Consumer Awareness and Attitude towards Nutritional Milk Products for People with Metabolic Syndrome - Nga, Bui Thi; Cuong, Tran Huu; Nga, Vu Thi Hang; Phuong, Nguyen Van (International Journal of Social Sciences and English Literature, 2025)
This article examines consumers’ awareness and attitudes regarding nutritional milk products designed for people with metabolic syndrome. Data were collected from 612 dairy product consumers in three major cities representing different regions of Vietnam: 204 in Hanoi, 203 in Da Nang, and 205 in Ho Chi Minh City. The study shows that the market for nutritional milk for people with metabolic syndrome is facing a paradox: consumers clearly understand the benefits and have positive feelings about the product, but are hindered by factors related to price, distribution, and a large gap in awareness of the difference and unique value of nutritional milk compared to regular milk. The study proposes solutions for dairy companies and relevant stakeholders to encourage consumer adoption, thereby transforming positive perceptions into sustainable consumption attitudes.